The Influence of Work Conflict and Organizational Commitment on Job Satisfaction - Intania Ayick Pratiwi; Enang Narlan SAP (Almana : Jurnal Manajemen dan Bisnis, 2021)
Job Satisfaction is a very important factor and is used as a benchmark for whether or not a company is good, Work Conflict and Organizational Commitment can help in achieving good Job Satisfaction. Therefore, work conflict and commitment are closely related to job satisfaction. The purpose of this study was to find out how Work Conflict, Organizational Commitment, and Job Satisfaction are applied by PT. A And One Precision Bintan, and to find out how much influence Job Conflict has on Job Satisfaction, the effect of Organizational Commitment on Job Satisfaction and the influence of Work Conflict and Organizational Commitment on Job Satisfaction. This study is a population study in which all employees are respondents in the study, for data collection using a questionnaire with a total of 75 respondents. The analytical method used is a quantitative method with descriptive analysis and verification analysis (path analysis). The results of the study stated that work conflict was in the category of frequent occurrences, the organizational commitment was in the good enough category, job satisfaction was in the good enough category. The result of path analysis shows that work conflict affects job satisfaction, organizational commitment affects job satisfaction.